ETNOGRAFI GAWAI DALAM PERKAWINAN SUKU TALANG MAMAK DI DESA TALANG SUNGAI LIMAU KECAMATAN RAKIT KULIM - Agustar Agustar; Pawennari Hijjang; Muhammad Yazid Fauzi; Rasni Andriani (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2022)
This study discusses the meaning of Gawai in the marriage of the Talang Mamak tribe in the village of Talang Sungai Limau, Rakit Kulim sub-district, the Gawai Ritual is a series of marriage rituals for the indigenous Talang Mamak tribe which includes a series of traditional pre-wedding processions until the device is implemented. The process of getting to the gadget goes through quite complicated stages starting from visiting a woman's house (betandang). taking things from men as a symbol of the seriousness of the relationship (bebibitan). The woman's family goes to the man's family asking for the seriousness of the relationship (menyulu) pick-up, three days left at each bride's house (balek-balekan) until the procession of the marriage contract (sembah mertua), the Gawai ritual has a symbol of meaning contained in it. . This study uses an ethnographic approach to obtain data and interpret data, where the ritual of the gawai is the main focus of this study. There are sacralizations and symbols in gadgets, not only objects but also motion and speech. Gambling and fighting as a form of negotiation between humans and supernatural beings so as not to interfere with the running of the device.